Pemprosesan Kimia ke atas Buangan Pertanian Padi - Lajis, Md Nordin; Mohd Sharif, Atan; Sukari, Mohd Aspollah (1984)
The production process of 2-furaldehyde (furfural) from agricultural wastes including the husk, leaf and straw was investigated chemically. Three types of pro tic acid were tested with respect to its cataly tic activity. The effect of hydrochloric acid concentration on the yield percentage was also investigated.